Diagnostic value of contrast-enhanced CT scans in identifying lung adenocarcinomas manifesting as GGNs (ground glass nodules). Issue 43 (October 2017) - Gao, Feng; Li, Ming; Sun, Yingli; Xiao, Li; Hua, Yanqing
Abstract : Abstract: This study aimed to explore the value of contrast-enhanced computed tomography (CT) scans in the differential diagnosis of atypical adenomatous hyperplasia, adenocarcinoma in situ, minimal invasive adenocarcinoma (MIA), and invasive adenocarcinoma (IAC), which manifested as ground glass nodules (GGNs) or mixed GGNs. Unenhanced and contrast-enhanced presurgical CT images of 136 cases of GGNs were compared. The nodules were diagnosed based on their solid portions and maximum dimensions, and the findings obtained using both contrast-enhanced and unenhanced CT images were analyzed in corroboration with the pathological diagnosis. Most (53/56) preinvasive nodules showed increased mean CT values after contrast administration. In the MIA group, after contrast administration, enlargements of the solid portions were seen in 48 nodules (48/60), and the elevation of the mean CT value was observed in 12 nodules (12/60). The vast majority of IAC nodules (29/30) showed enlargement of the solid portions after contrast administration. Moreover, for group differences, findings obtained using this approach statistically match the pathological findings. Contrast-enhanced CT scans are more useful than unenhanced CT scans for the diagnosis of GGNs, especially for pure GGNs, before surgery.